Stem cells and metabolic diseases. (21st May 2008) - Bernardo, Andreia S.; Docherty, Kevin
Abstract : Obesity is a metabolic disorder, which has been recognized as a global epidemic. It contributes to insulin resistance, the major cause of Type 2 diabetes, as well as to the development of other related diseases. Our basic premise is that a better understanding of how adult stem cells of the pancreas contribute to the maintenance of the pancreatic β-cell pool against the increased metabolic demands associated with obesity may provide new therapeutic targets for treating diabetes. At the same time, if we knew more about the biology of adipocyte formation, maintenance and deposition in obese individuals, perhaps some control over the adipocyte tissue mass of these individuals would be facilitated and treatment of obesity would become available. Many investigations in the field are therefore aimed at describing how adipocyte stem cells function in the various sites of fat deposition and the extent to which these stem cells contribute to both brown and white adipocytes. Studies on the differentiation of human embryonic stem cells along the pancreatic and adipocyte lineages may therefore better inform approaches to these studies.